The beauty and complexity of the small heat shock proteins: a report on the proceedings of the fourth workshop on small heat shock proteins - Ecroyd, H; Bartelt-Kirbach, B; Ben-Zvi, A; Bonavita, R; Bushman, Y; Casarotto, E; Cecconi, C; Lau, WCY; Hibshman, JD; Joosten, J; Kimonis, V; Klevit, R; et al. (Springer, 2023)
The Fourth Cell Stress Society International workshop on small heat shock proteins (sHSPs), a follow-up to successful workshops held in 2014, 2016 and 2018, took place as a virtual meeting on the 17-18 November 2022. The meeting was designed to provide an opportunity for those working on sHSPs to reconnect and discuss their latest work. The diversity of research in the sHSP field is reflected in the breadth of topics covered in the talks presented at this meeting. Here we summarise the presentations at this meeting and provide some perspectives on exciting future topics to be addressed in the field.